¹S₀-luminescence in Ca₁₋ₓPrxF₂₊ₓ crystals - Boiaryntseva, I.A.; Shiran, N.V.; Gektin, A.V.; Stryganyuk, G.B.; Belsky, A.N.; Shimamura, K. (Functional Materials, 2012)
Luminescence properties of CaF₂:Pr (0.2 mol %) and Ca₀.₆₅Pr₀.₃₅F₂.₃₅ crystals were studied at 10 K. Excitation and emission spectra show two types of the Pr³⁺ centers with the typical ¹S₀ —> 4f² radiative transitions. High level of rare-earth ions aggregation in CaF² and peculiarities of the defect structure in Ca₁₋ₓPrₓF₂₊ₓ solid solutions point to the formation of Pr²⁺-based clusters. Emission from ¹S₀-level is attributed to Pr³⁺ ions included in the clusters.